Parental unemployment and the transition into tertiary education: Can institutions moderate the adverse effects? - Kristina Lindemann; Markus Gangl (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper examines how parental unemployment affects the transition to postsecondary education in different institutional contexts. Drawing on theoretical perspectives in intergenerational mobility research and sociology of higher education, we estimate the extent to which these intergenerational effects depend on social and education policies. We use data from five longitudinal surveys to analyze effects of parental unemployment on entry to postsecondary education in 21 countries. The results of multilevel regression analysis show that contexts providing better insurance against unemployment in terms of generous earnings replacement alleviate the adverse effect of parental unemployment. Moreover, entry gaps between youth from unemployed and employed households are smaller in tertiary education systems with more opportunity-equalizing education policies that provide higher financial support to students and reduce the role of private expenditure. We also find that these education policies are more relevant for children of less-educated unemployed parents.
Keywords: 330; cross-country comparison; intergenerational effects; education policy; parental unemployment; social policy; transition to postsecondary education